Answer:
3 ln(x − 1) − 3/(x − 1) + C
Step-by-step explanation:
∫ 3x / (x − 1)² dx
3 ∫ x / (x − 1)² dx
If u = x − 1, then x = u + 1, and du = dx.
3 ∫ (u + 1) / u² du
3 ∫ (1/u + 1/u²) du
3 (ln u − 1/u + C)
3 ln u − 3/u + C
Substitute back:
3 ln(x − 1) − 3/(x − 1) + C
Answer:
If there are an even number (0, 2, 4, ...) of negative factors to multiply, the product is positive. If there are an odd number (1, 3, 5, ...) of negative factors, the product is negative.
Step-by-step explanation:
Answer:
h(-4) = -4
Step-by-step explanation:
Since x is given (x = -4). Then, all you need to do is log in -4 for each value of x
h(-4) =
−
(
−
4
)
2
-3(-4)
h(-4) = -(16) + 12 = -4
According to my examination I have confirmed that I do NOT repeat do NOT know this.